PROPORSI PEMBERIAN RANSUM YANG BERBEDA PADA PAGI, SIANG, DAN MALAM TERHADAP RESPON FISIOLOGIS DAN PRODUKSI SAPI PERANAKAN SIMENTAL - Nia Yuliyanti; Erwanto ,; Siswanto . (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
The objective of this research is to know the influence of the proportion of the distribution of feed in the morning, afternoon, and night toward physiological and production response of Simental Cattle Grade. The parameters measured is respiration rate, heart rate, body temperature, dry matter intake, average daily gain, and feed convertion ratio. This research is implemented by using Randomized Block Design (RBD) with three treatment and four group. Beef cattle used is bull of Simental Cattle Grade with body weights 330—420 kg. The treatment that used is proportion of the distribution of feed 33,3% morning, 33,3% afternoon, 33,3% night (P1); 50% morning, 25% afternoon, 25% night (P2); and 25% morning, 25% afternoon, 50% night (P3). The data from this research is tested by using analyzed of variance and continued with Least Significance Difference (LSD). The result of this research shows that by the proportion of the distribution of feedin different in the morning, afternoon, and night have positive influence (P<0,05) toward physiological response on the respiration rate, and heart rate, but have not positive influential (P>0,05) toward body temperature and response of production on the dry matter intake, average daily gain, and feed conversion ratio. The proportion of feed (P3) is the best treatment to the physiological response of cattle and no treatment that gives the best production response.